BENJAMIN’S ANXIETY IN MASON DEAVER’S I WISH YOU ALL THE BEST - Lukman Hakim; Linusia Marsih (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
This thesis discusses the issues of anxiety reflected in Deaver’s I Wish You All the Best. It aims to describe three problems related to anxiety, namely Benjamin’s anxiety reflected in the novel, the core issues of Benjamin’s anxiety, and the impacts of Benjamin’s anxiety on himself. In doing the analysis, Freudians’ theories of psychoanalysis are applied. This belongs to descriptive qualitative study because the data of the research are qualitative data and the results of the analysis are presented descriptively. The result of the analysis shows that three types of anxiety are suffered by Benjamin. They are neurotic anxiety, moral anxiety, and realistic anxiety. Benjamin's anxiety is triggered by his repressed wounds and unresolved conflict aggravated by his parent's rejection. In addition to the repressed wounds and unresolved conflict, other core issues that lead to Benjamin's anxiety are threat, fear, and repression. Benjamin's anxiety affects his physical and mental health. After doing the analysis, the researcher finds out that Benjamin’s anxiety arises from the environment, especially parental factors that trigger fears and then manifest into anxiety. It can be inferred that poor parenting has a great influence on determining the future condition of a child. Parents should apply good parenting to avoid future bad impacts on children’s lives.